Leptin and Obesity: Role and Clinical Implication - Obradovic, Milan; Sudar-Milovanovic, Emina; Soskic, Sanja; Essack, Magbubah; Arya, Swati; Stewart, Alan J.; Gojobori, Takashi; Isenovic, Esma R. (Frontiers in Endocrinology, 2021)
The peptide hormone, leptin, regulates food intake, body mass, and reproductive function and plays a role in fetal growth, proinflammatory immune responses, angiogenesis, and lipolysis. Leptin is a product of the obese (ob) gene and, mainly produced in and secreted from fat cells in white adipose tissue, that binds to and activates its cognate receptor, the leptin receptor (LEP-R). The distribution of LEP-R facilitates the pleiotropic effects of leptin, playing a crucial role in the regulation of body mass via a negative feedback mechanism between adipose tissue and the hypothalamus. Leptin resistance is characterized by reduced satiety, over-consumption of nutrients, and an increase in total body mass. Often this leads to obesity, which reduces the effectiveness of using exogenous leptin as a therapeutic agent. Thus, combining leptin therapies with leptin sensitizers may help overcome such resistance and, consequently, obesity. In this review, we examine recent data obtained from human and animal studies related to leptin, its role in obesity, and its usefulness in obesity treatment.